2016
DOI: 10.1016/j.cose.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Information system security commitment: A study of external influences on senior management

Abstract: From the beginning, a completed dissertation was the goal, but the real value was in the process, not the product. The dissertation demonstrates the ability of a researcher to complete a significant study, but only after the process provides the skills in conceiving and justifying a research idea, designing a study, collecting and analyzing the data, and finally reporting the results. The process was rewarding in its own right. I sincerely thank my advisor and committee chairperson, Dr. Gurvirender Tejay, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 177 publications
(491 reference statements)
0
57
0
1
Order By: Relevance
“…The cybersecurity community has recently begun making efforts to intervene by involving and educating top-level managers and executives. This approach is wellsupported by the research findings that: 1) Commitment by top executives is essential for adoption, implementation, and assimilation of security capabilities [97][98][99]; and 2) Cybersecurity concerns affect an entire organization (not just IT departments or isolated response teams) [100,101]; hence, the responsibility for addressing such issues should belong to managers at higher organizational levels.…”
Section: Implications For Practicementioning
confidence: 99%
“…The cybersecurity community has recently begun making efforts to intervene by involving and educating top-level managers and executives. This approach is wellsupported by the research findings that: 1) Commitment by top executives is essential for adoption, implementation, and assimilation of security capabilities [97][98][99]; and 2) Cybersecurity concerns affect an entire organization (not just IT departments or isolated response teams) [100,101]; hence, the responsibility for addressing such issues should belong to managers at higher organizational levels.…”
Section: Implications For Practicementioning
confidence: 99%
“…Executive commitment and support of IT in general, [12,13] and of information security in particular, is a well-studied area [14,15]. Research shows that commitment by top executives is essential for adoption, implementation, and assimilation of security capabilities [16][17][18]. Moreover, the importance of being proactive in cybersecurity capability development is well understood-it is more cost effective than taking a reactionary approach and reduces failure rates [19].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the information quality was positively correlated with the user satisfaction; the system quality was negatively related to the user satisfaction, while the service quality was not related to the user satisfaction. Therefore, the relationship between quality variables has shown a positive relationship between them, except in the case of information quality and service quality [30].…”
Section: Information Systems Security Successmentioning
confidence: 97%
“…Security requirements or data sensitivity are nothing lesser in small and mediumsized organizations than large, but small and medium-sized businesses face the challenge of lacking support for information security management due to insufficient awareness of its importance [10]. That is why they, instead of proactive, take reactive attitude according to information security, and consider security technologies as business costs rather than strategic potentials [29] resulting in greater resource constraints and education and training shortages in information systems security domain [30]. Due to the limited number of employees and technical constraints, small and medium-sized companies often have system administrator who is responsible for system configuration as well as system security management i.e.…”
Section: Information Security In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation